Additional constraints to ensure three vanishing moments for orthonormal wavelet filter banks and transient detection - Uzinski, Julio Cezar; Paiva, Henrique Mohallem; Villarreal, Francisco; Duarte, Marco Aparecido Queiroz; Galvão, Roberto Kawakami Harrop (Trends in Computational and Applied Mathematics, 2015)
<!--StartFragment-->This article presents an improvement to the formulation of Sherlock and Monro for the wavelet parameterization for the obtainment of the restrictions which ensure three vanishing moments. In order to test the formulation presented, a transient signal detection is presented.<!--EndFragment-->